1992
DOI: 10.1128/jcm.30.9.2419-2426.1992
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and molecular characterization of bat rabies virus in Europe

Abstract: The predominant role of Eptesicus serotinus in the epizootic of bat rabies in Europe was further outlined by the first isolation of the rabies virus from this species in France. The distribution of the virus was studied in naturally infected E. serotinus bats at the time of death and suggested that the papillae of the tongue and the respiratory mucosa may play a role in virus production and excretion. The analysis of 501 French rabies virus isolates from various animal species by antinucleocapsid monoclonal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(65 citation statements)
references
References 30 publications
(34 reference statements)
0
58
1
2
Order By: Relevance
“…The presence of EBLVs in Europe was first documented in 1954 (Kappelar, 1989;King et al, 2004), and during the period 1977-2004, 783 EBLV confirmed cases (by isolation of viral RNA) have been reported (King et al, 2004;Mü ller, 2000;Rabies Bulletin Europe, 2001, 2003. EBLV-1 (genotype 5) and EBLV-2 (genotype 6) are related to, but can be genetically and antigenically distinguished from classical rabies (RABV: genotype 1) (Bourhy et al, 1992(Bourhy et al, , 1993(Bourhy et al, , 1999Badrane et al, 2001). In addition, both EBLVs can be distinguished from each other using sequence analysis of the N and/or G genes (Fooks et al, 2003a).…”
Section: Eblvsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of EBLVs in Europe was first documented in 1954 (Kappelar, 1989;King et al, 2004), and during the period 1977-2004, 783 EBLV confirmed cases (by isolation of viral RNA) have been reported (King et al, 2004;Mü ller, 2000;Rabies Bulletin Europe, 2001, 2003. EBLV-1 (genotype 5) and EBLV-2 (genotype 6) are related to, but can be genetically and antigenically distinguished from classical rabies (RABV: genotype 1) (Bourhy et al, 1992(Bourhy et al, , 1993(Bourhy et al, , 1999Badrane et al, 2001). In addition, both EBLVs can be distinguished from each other using sequence analysis of the N and/or G genes (Fooks et al, 2003a).…”
Section: Eblvsmentioning
confidence: 99%
“…Active infection (replicating virus in the CNS and/or excretion of virus in saliva) caused by EBLV-1 has not been recorded in the UK to date, and the disparity between EBLV-1 records in Europe and the UK may be related to the limited geographical distribution and population size of E. serotinus within the UK. Spillover of EBLV-1 (Table 6) into sheep has occurred on two separate occasions in Denmark, in 1998(Ronsholt, 2002Tjørnehøj et al, 2006), and into a stone marten in Germany (Mü ller et al, 2001), a domestic cat (antibodies only) in Denmark (Tjørnehøj et al, 2004) and one confirmed human case (Selimov et al, 1989;Bourhy et al, 1992). A further two unconfirmed human cases of suspected bat origin have also been reported (Table 6) (Rabies Bulletin Europe, 1986;Botvinkin et al, 2006).…”
Section: Eblv-1mentioning
confidence: 99%
“…Advances in molecular biology and a better understanding of RABV pathogenesis have led to new approaches to address the problem. Of all options, we consider the RABV polymerase complex to represent the most promising target for direct-acting antivirals due to the comparably low conservation of G across lyssaviruses [12,17,158,174,[189][190][191][192]. The heterologous polymerase complex offers druggable protein-protein interfaces, essential enzymatic centers, and opportunity for allosteric and competitive substrate-analog inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) targeting RABV G have proven antiviral efficacy [15,[152][153][154]. Broad panels of antibodies against rabies G revealed primary clusters for antibody recognition in distinct regions of the G ectodomain [18,[155][156][157][158]. As shown in figure 5, these antigenic sites (AS) include ASI (a.a. 226-231), ASII (a.a. [34][35][36][37][38][39][40][41][42], ASIII (a.a.330-338), ASIV (a.a. 251), ASV (a.a. 261-264), and ASVI (a.a. 264).…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…Indeed, EBLV-1 is antigenically and genetically more closely related to Duvenhage virus than it is to EBLV-2. 26 EBLV-2 was isolated from a zoologist who died in Finland with what was diagnosed as rabies. 27 Similar viruses were isolated from pond bats (Myotis dasycneme) in The Netherlands.…”
Section: European Bat Lyssavirusmentioning
confidence: 99%